Pericardial Effusion and Cardiac Tamponade in Neonatal Emergencies: Sudden Death Linked to TPN via Central Venous Catheterization — A Multidisciplinary Perspective Involving Radiology, Clinical Nutrition, Pharmacy, and Nursing - Alenezi, Anwar Hwayan; Alotabi, Talal Abdulmuin; Alshuwaer, Thamer Abdullah; Alonazi, Monifa Jadid; Ibrahim, Marwah Mohammedsagher; Al Hazmi, Fatimah Hamoud; Alatawi, Fatmah; Alonizi, Rehan Abdulhay; Qahtan , Sumaya Ahmed; Almalki, Maryam Saeed (Journal of Posthumanism, 2024)
Pericardial effusion (PE) and cardiac tamponade (CT) are rare but potentially fatal complications in neonates receiving total parenteral nutrition (TPN) via central venous catheterization (CVC). These events are often linked to catheter tip malposition or migration, coupled with the chemical toxicity of hyperosmolar TPN solutions.This narrative review explores the pathophysiology, clinical presentation, diagnostic challenges, and multidisciplinary management of TPN-related PE/CT in neonates.We reviewed case reports, clinical studies, and meta-analyses published between 2013 and 2023, focusing on emergency medicine, radiology, nutrition, pharmacy, and nursing roles. Tables were included to summarize reported cases, discipline-specific findings, and research insights.Findings highlight the critical importance of point-of-care ultrasound (POCUS) in early diagnosis and catheter tip verification. Successful outcomes are associated with timely pericardiocentesis, vigilant nursing observation, and safe TPN formulation. Multidisciplinary safety protocols and routine imaging significantly reduce morbidity and mortality.Preventing neonatal cardiac tamponade requires a collaborative approach, involving accurate catheter placement, real-time monitoring, and prompt multidisciplinary response. Routine POCUS and cross-disciplinary vigilance are essential to improving outcomes in neonatal intensive care units.